2015
DOI: 10.1039/c5ra10442d
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient NIR to visible upconversion in a ZnO:Er,Yb thin film deposited by a AACVD atmospheric pressure process

Abstract: A ZnO:Er,Yb hexagonal wurtzite phase structured thin film with highly efficient NIR to visible upconversion emissions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…2 (d)–(f) show that the particles became spherical, and uniformly residing on irregular shapes. The slight change in morphology at higher substrate temperatures can be attributed to the nucleation process of ZnTiO 3 : Er 3+ ,Yb 3+ compound onto the surface of the Si substrate due to higher deposition temperature [ 19 ]. The elemental composition was determined using EDS spectroscopy.…”
Section: Resultsmentioning
confidence: 99%
“…2 (d)–(f) show that the particles became spherical, and uniformly residing on irregular shapes. The slight change in morphology at higher substrate temperatures can be attributed to the nucleation process of ZnTiO 3 : Er 3+ ,Yb 3+ compound onto the surface of the Si substrate due to higher deposition temperature [ 19 ]. The elemental composition was determined using EDS spectroscopy.…”
Section: Resultsmentioning
confidence: 99%
“…One possibility not explored yet in this review is that of thin-film UC layers, however, there are very few results reported of thin films exhibiting high enough quality to be able to report a ϕ UC value. Elleuch et al realized a ZnO:Yb 3+ /Er 3+ films of ∼310 nm thickness that was grown on large area (7.5 cm × 7.5 cm) on Si (111) substrates at 430 °C via an aerosol-assisted chemical vapor deposition process . As deposited, the ϕ UC values of the films remained low at about 1–1.4%, however, upon annealing at 1000 °C, the ZnO:9% Yb 3+ /3% Er 3+ increased up to 5.6 ± 0.1% at a power density of 19.3 W cm –2 .…”
Section: Discussionmentioning
confidence: 99%
“…Elleuch et al realized a ZnO:Yb 3+ /Er 3+ films of ∼310 nm thickness that was grown on large area (7.5 cm × 7.5 cm) on Si (111) substrates at 430 °C via an aerosol-assisted chemical vapor deposition process. 247 As deposited, the ϕ UC values of the films remained low at about 1−1.4%, however, upon annealing at 1000 °C, the ZnO:9% Yb 3+ /3% Er 3+ increased up to 5.6 ± 0.1% at a power density of 19 via aerosol-UV assisted metal−organic chemical vapor deposition at 410 °C followed by an 800 °C annealing step. 248 The trend of increasing quantum yield with process temperature from before is repeated, with as-deposited samples exhibiting a ∼0.6% ϕ UC , increasing to 4.1 ± 0.1% for the best performing sample (Y 2 O 3 :2% Er 3+ ) when excited at 978 nm (19.3 W cm −2 ).…”
Section: Uc Engineeringmentioning
confidence: 99%
“…Due to their low phonon energy, they provide a very low rate of nonradiative recombination, promoting the photoluminescence process. While numerous pioneering works have been published on spectral conversion using rare earth doped ZnO and ITO oxide thin films, SnO 2 has been much less considered as a potential alternative host material. Nevertheless, SnO 2 has a gap of about 3.6 eV (bulk material), which offers a good absorption in the UV region while being transparent to visible and NIR photons.…”
Section: Introductionmentioning
confidence: 99%